Strengthening respectful communication with patients and colleagues in neonatal units — developing and evaluating a communication and emotional competence training for nurse managers in Kenya [version 2; peer review: 2 approved] - Mwanamvua Boga; Dorothy Oluoch; Jacinta Nzinga; Sassy Molyneux; Mike English; Ane Haaland; Peris Musitia (Wellcome Open Research)
Introduction Effective communication is essential to delivering compassionate, high-quality nursing care. The intensive, stressful and technical environment of a new-born unit (NBU) in a low-resource setting presents communication-related challenges for nurses, with negative implications for nurse well-being, team relationships and patient care. We adapted a pre-existing communication and emotional competence course with NBU nurse managers working in Kenya, explored its’ value to participants and developed a theory of change to evaluate its’ potential impact. Methods 18 neonatal nurse managers from 14 county referral hospitals helped adapt and participated in a nine-month participatory training process. Training involved guided ‘on the job’ self-observation and reflection to build self-awareness, and two face-to-face skills-building workshops. The course and potential for future scale up was assessed using written responses from participant nurses (baseline questionnaires, reflective assignments, pre and post workshop questionnaires), workshop observation notes, two group discussions and nine individual in-depth interviews. Results Participants were extremely positive about the course, with many emphasizing its direct relevance and applicability to their daily work. Increased self-awareness and ability to recognize their own, colleagues’ and patients’ emotional triggers, together with new knowledge and practical skills, reportedly inspired nurses to change; in turn influencing their ability to provide respectful care, improving their confidence and relationships and giving them a stronger sense of professional identity. Conclusion Providing respectful care is a major challenge in low-resource, high-pressure clinical settings but there are few strategies to address this problem. The participatory training process examined addresses this challenge and has potential for positive impacts for families, individual workers and teams, including worker well-being. We present an initial theory of change to support future evaluations aimed at exploring if and how positive gains can be sustained and spread within the wider system.